Chronic Pain: Clinical Updates and Perspectives - Galvez-Sánchez, Carmen M.; Montoro Aguilar, Casandra Isabel; Hollmann, Markus W. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint provides an essential comprehensive overview of chronic pain research. New research developments, clinical updates and treatments' perspectives in chronic pain-in general and specific chronic pain conditions, with a particular focus on chronic noncancer pain, cancer pain, chronic tension-type headaches, chronic neck pain, shoulder pain, chronic back pain, fibromyalgia syndrome, and degenerative lumbar spinal stenosis-are described and discussed. Future trends on the topic are also covered.